Optimizing Growth and Yield of Purple Eggplants using Rice Washing Water as Organic Fertilizer: Optimalisasi Pertumbuhan dan Hasil Tanaman Terong Ungu Menggunakan Air Cucian Beras sebagai Pupuk Organik - Cahyono, Mauludin (Indonesian Journal of Innovation Studies, 2023)
This study aimed to investigate the impact of rice washing water on the growth and yield of purple eggplants, and to determine the optimal dosage of rice washing water for achieving the highest growth and yield. The research was conducted at Muhammadiyah University of Sidoarjo's Land in Graha Pesona Modong Housing, Tulangan, Sidoarjo, using a field experiment with Randomized Group Design (RAK) pattern. The experiment consisted of one factor with seven treatment levels, replicated three times, ranging from 100 ml/liter to 400 ml/liter of water. Observations included plant height, number of leaves, number of fruits, root length, and fruit weight. The data was analyzed using ANOVA and BNJ for significant differences. The results revealed that liquid organic fertilizer from rice washing water had no effect on plant height and number of fruits, but significantly influenced the number of leaves, fruit weight, and root length. The optimal dosage for the highest fruit weight was 300 ml, while the highest root length was achieved at a dosage of 200 ml. Highlights: Investigated the impact of rice washing water as an organic fertilizer on purple eggplant growth and yield. Utilized a Randomized Group Design with varying dosages of rice washing water to determine the optimal application. Found that the combination of rice washing water significantly affected the number of leaves, fruit weight, and root length, providing valuable insights for sustainable agriculture practices.